Lifestyle diseases: Health in the contemporary city - T. S. Martynenko (RUDN journal of Sociology, 2021)
The article presents an overview of studies of the factors that affect health in the contemporary city. The increase in the urban population makes it necessary to analyze factors (environmental, social, etc.) and features of the urban structure in terms of their impact on the quality and standards of living. However, assessments of the city in the study of healthy lifestyle are contradictory. On the one hand, researchers emphasize the availability of medical care, effective fight against infectious diseases, and numerous attempts to transform the visual urban space. On the other hand, researchers stress the spatial inequality of the urban structure (for example, in access to health care), the spread of noncommunicable and lifestyle diseases in cities, the destruction of social ties and the problem of loneliness. Therefore, it is necessary to systematize the current research, identify the main risks of urban lifestyle, and discuss the role of social sciences in such interdisciplinary studies. The proposed typology of health research in the contemporary city is based on Yu.P. Lisitsyns ratio of factors that determine the level of health. Although many studies claim an integrated approach, the analysis showed that most of them present one of three approaches: the study of sanitary-hygienic features of the urban space (or its medical aspects); the study of ecology and architecture of the urban space; the study of social-psychological features of the urban lifestyle. The systematization of the main risks of the urban lifestyle allowed the author to identify the priority areas of its study. Thus, based on the features of the covid-19 pandemic in cities, the author argues that there is a need for more active participation of sociologists in the discussion of both infectious and non-communicable diseases, which should focus on social factors of their spread, course, prevention and control.